Motivasi Konsumen Generasi Z dalam Keputusan Pembelian Tas Merek Mossdoom : Studi Kasus Mahasiswa KPI angkatan 23 UIN Saizu - Marifatul kamalia Fadilah; Naely Nisfatun Nasiroh (Kajian Administrasi Publik dan ilmu Komunikasi, 2026)
This study aims to explore the motivations of Generation Z in making purchasing decisions regarding the local bag brand Mossdom. Generation Z is recognized as a digital generation whose consumption preferences are influenced by emotions, trends, and exposure to social media. This research adopts a descriptive qualitative approach using a case study method. Data were collected through semi-structured interviews with five respondents aged 19 to 21 years, all of whom are university students and active users of Mossdom products. The findings reveal that purchasing decisions are influenced by a combination of emotional factors such as pride and self-confidence, rational factors such as affordable prices, trendy designs, and product functionality, social factors including peer and family influence, and digital media factors such as influencer reviews and e-commerce platforms. The influence of social media is notably high, ranging from 70 percent to 80 percent. These results indicate that Mossdom has successfully built a positive brand image as a local product that aligns with the lifestyle of Generation Z. The study implies the importance of consistent product quality, innovative design, and adaptive digital marketing strategies to effectively engage young consumers in the digital era.